INFLUENCE OF POP UP BOOK MEDIA USE ON THE LEARNING OUTCOMES OF IPAS GRADE 4 SD MUHAMMADIYAH 1 KEDUNGGALAR - Syalikah prety dwi agustinai; Uci Ulfa Nur'afifah; Budi Rachman (SOSIOEDUKASI, 2025)
Natural and Social Sciences (IPAS) education at the elementary school level has an important role as a means for students to get to know themselves, understand the surrounding environment, and apply the knowledge gained in daily life. The lack of variety in the learning process can result in students having difficulty understanding the material being taught. The use of conventional methods such as lectures is one of the main causes. The type of research used is using a quantitative approach with the Pre-Experimental Design type. The researcher used the One Group Pretest-Posttest Design research design to be carried out in one class without a comparison class using a pretest before being given treatment. With that, the results of the treatment can be known more accurately, because it can be compared with the situation before being given treatment. The results of this study are that there is a significant influence of the use of Pop Up Book media on the reading ability of 4th grade students of SD Muhammadiyah 1 Kedunggalar